Evaluation of the ecological carrying capacity of Wailingding marine ranching in Zhuhai, China by high-resolution remote sensing - Wang, Ziwen; Yao, Lijun; Yu, Jing; Chen, Pimao; Li, Zhen; Yang, Weiwei (Frontiers in Marine Science, 2024)
Evaluation of ecological carrying capacity of marine ranching is a prerequisite and guarantee for ensuring the sustainable development of aquaculture activities, protecting and maintaining the stability and security of marine ecosystems. Based on high-resolution satellite remote sensing data and survey data of Wailingding marine ranching in Zhuhai from 2006 to 2021, this study constructed marine ecological carrying capacity (MECC) index system with 3 levels: resources, environment and ecology. A combination of Analytic Hierarchy Process (AHP) method and entropy method was applied to assign values to index, and then, the MECC of marine ranching was evaluated based on state-space model and the Weighted Bonferroni Mean (WBM) model. Results showed that MECC of Wailingding marine ranching increased from 0.49 ( 2006) before the marine ranching construction to 0.79 (2021) after the marine ranching construction. Marine ranching had elevated MECC from a loadable state to a fully loaded state. The intertidal subsystem, with a weight of 52.51%, dominates the MECC of marine ranching, in which resource and environmental factor are the major influencing factors. The increase rate of state-space model (61.73%) was higher than that of the WBM model (44.34%), indicating that state-space model is more feasible for the MECC assessment of Wailingding marine ranching.